Patient’s Satisfaction with Coronary Artery Disease Concerning Medical Care Services at Teaching Hospitals in Erbil City - Srusht Dhahier ismael; Yousif Mohammad Younis (Erbil Journal of Nursing and Midwifery, 2025)
Background and Objectives: Coronary artery disease is now broadly recognized as a major global health issue. Patient’s satisfaction with medical care services is an important health outcome. The study was to assess the satisfaction level of patients with coronary artery disease concerning medical care services and to find out the difference between patients’ satisfaction and the socio-demographic characteristics of the patients.